Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I didn't get this method. $3a^2-9a+6 = 3(a^2-3a+2) = 3(a^2-1a*3+3^2-3^2+2)=$ $= 3[(a-3)^2-7]$, then?

share|improve this question
2  
Yes, then what? What are you trying to accomplish? –  Hans Lundmark Oct 24 '10 at 13:26
1  
By the way, the last equality is wrong. $(a-3)^2=a^2-6a+9$, not $a^2-3a+9$. –  Hans Lundmark Oct 24 '10 at 13:34
    
@Hans to continue... The answer is 3(a-2)(a-1) but how to get it? –  lam3r4370 Oct 24 '10 at 13:38
add comment

4 Answers 4

up vote 7 down vote accepted

Ah, so you want to factor the polynomial. Here's how:

$$3(a^2-2 \frac{3}{2} a + 2) = 3\left(\left(a-\frac{3}{2}\right)^2 - \frac{9}{4} + 2\right) = 3\left(z^2 - \frac{1}{4}\right)$$ $$= 3\left(z-\frac{1}{2}\right)\left(z+\frac{1}{2}\right) = 3(a-2)(a-1),$$ where I temporarily used the substitution $z=a-\frac{3}{2}$.

share|improve this answer
4  
And of course, when you are done you should multiply out $3(a-2)(a-1)$ to check that you really get back to the polynomial that you started with! (Just to verify that you haven't made any errors during the calculation.) –  Hans Lundmark Oct 24 '10 at 13:55
add comment

There is also a simple way that involves no fraction calculation,it goes like this :

$ 3a^{2}-9a+6 $

$ = 3a^{2}-6a-3a+6 $

$ = a(3a-6)-(3a-6) $

$ = (3a-6)(a-1) $

$ = 3(a-1)(a-2) $

share|improve this answer
3  
Simple once you know the answer. ;) Not much of a general method, however. –  Hans Lundmark Oct 24 '10 at 17:13
1  
I disagree,this is how I was taught to factorize a quadratic equation in school :) –  Quixotic Oct 24 '10 at 23:05
1  
So how would you do $3a^2-9a+5$? –  Hans Lundmark Oct 25 '10 at 9:18
add comment

You can guess and then confirm that $a=1$ is a zero of $3a^{2}-9a+6$. Thus you can factor it as

$3a^{2}-9a+6=3(a-1)(a-x)=3x-3a-3ax+3a^{2}$

and solve for $x$. Comparing the coefficients of $a^{2},a,a^{0}$, you get

$3=3,3x=6,-3-3x=-9$,

which is equivalent to $x=2$ and $1+x=3$. Hence $x=2$ and

$3a^{2}-9a+6=3(a-1)(a-2)$.

share|improve this answer
add comment

If you desire to factor it by way of completing the square then it is simpler to first multiply by 4, namely

$$\rm\ \ 4\:(a^2-3\: a+2)\ =\ (2\:a-3)^2 - 1\ =\ (2\:a-2)\:(2\:a-4)$$

Finally, divide both sides through by $\rm\ \: 4\ =\ 2\cdot 2$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.